Attempts to Demonstrate Hemagglutination and Hemadsorption by Respiratory Syncytial Virus - Richman, Alan V. (1971)
Extensive attempts to demonstrate a hemagglutinin of respiratory syncytial virus by both hemagglutination and hemadsorption tests failed. Hemagglutination tests were performed with red blood cells from 12 different animal species and at various temperatures and pH.